Hyperosmotic Shock Transiently Accelerates Constriction Rate in Escherichia coli - Sun, Jiawei; Shi, Handuo; Huang, Kerwyn Casey (Frontiers in Microbiology, 2021)
Bacterial cells in their natural environments encounter rapid and large changes in external osmolality. For instance, enteric bacteria such as Escherichia coli experience a rapid decrease when they exit from host intestines. Changes in osmolality alter the mechanical load on the cell envelope, and previous studies have shown that large osmotic shocks can slow down bacterial growth and impact cytoplasmic diffusion. However, it remains unclear how cells maintain envelope integrity and regulate envelope synthesis in response to osmotic shocks. In this study, we developed an agarose pad-based protocol to assay envelope stiffness by measuring population-averaged cell length before and after a hyperosmotic shock. Pad-based measurements exhibited an apparently larger length change compared with single-cell dynamics in a microfluidic device, which we found was quantitatively explained by a transient increase in division rate after the shock. Inhibiting cell division led to consistent measurements between agarose pad-based and microfluidic measurements. Directly after hyperosmotic shock, FtsZ concentration and Z-ring intensity increased, and the rate of septum constriction increased. These findings establish an agarose pad-based protocol for quantifying cell envelope stiffness, and demonstrate that mechanical perturbations can have profound effects on bacterial physiology.